MMP1 regulated by NEAT1/miR-361-5p axis facilitates the proliferation and migration of cutaneous squamous cell carcinoma via the activation of Wnt pathway. Issue 5 (3rd June 2021) - Jiang, Shiqiu; Liu, Hairong; Zhang, Jie; Zhang, Fang; Fan, Jiawei; Liu, Yueming
ABSTRACT: Cutaneous squamous cell carcinoma (CSCC) is one of the most malignant tumors worldwide. It has been validated that matrix metallopeptidase 1 (MMP1) expression was obviously up-regulated in CSCC tissues. However, its specific role in CSCC is still unclear. RT-qPCR analysis and western blot assays were used to measure the mRNA and protein expressions, respectively. MTT and colony formation assays were conducted to assess proliferative ability. Transwell assays were adopted to evaluate migratory and invasive abilities. Flow cytometry and caspase-3/8/9 activity assays were carried out to evaluate cell apoptosis. Relevant mechanism experiments were finally performed to delineate molecular relationship among genes. We found that the expression of MMP1 was up-regulated in CSCC cells, and knockdown of MMP1 suppressed cell proliferation and invasion in CSCC. Subsequently, miR-361-5p was validated to target MMP1. Moreover, miR-361-5p was proved to be sponged by nuclear paraspeckle assembly transcript 1 (NEAT1) in CSCC. We further demonstrated that NEAT1 could activate Wnt pathway to affect cell proliferation and invasion. Finally, miR-361-5p inhibition rescued the suppressing effects of NEAT1 depletion on cell proliferation, invasion as well as Wnt pathway in CSCC. In summary, MMP1 regulated by NEAT1/miR-361-5p axis facilitated CSCC malignant behaviors via Wnt pathway activation.